The Development of Mathematics Mobile Learning Media to Improve Students’ Autonomous and Learning Outcomes (Journal of Primary Education, 2019)
This study aims to (1) develop mobile learning as mathematics learning media; (2) test the practicality of the developed mathematics mobile learning media; and (3) test the effectiveness of mathematics mobile learning media that is developed towards the autonomous and learning outcomes of elementary school students. This type of research is research and development by adapting the ADDIE model. Product assessment is carried out by media experts, material experts, information technology experts, peer reviewers and trial. The research data was collected through a media assessment questionnaire and tests, then analysed with N-Gain and t-test. The results of this study are: (1) mathematics mobile learning media has been well structured by getting input from media expert validators, material experts, information technology experts, peer reviewers and students; (2) mathematics mobile learning media is considered feasible to be used in learning, in terms of material aspects, media aspects and students' test results, and (3) there is a significant increase between the autonomous and learning outcomes of students who take learning using mathematics mobile learning media with conventional learning. The results of this study indicate that the mathematics mobile learning media is feasible and effective to be used in elementary mathematics learning.